2023
DOI: 10.1186/s40634-023-00674-0
|View full text |Cite
|
Sign up to set email alerts
|

Intra‐articular injections in sport‐active patients with degenerative cartilage lesions or osteoarthritis of the knee: a systematic review

Luca De Marziani,
Alessandro Sangiorgio,
Alessandro Bensa
et al.

Abstract: Purpose The aim of this systematic review was to analyse the available clinical evidence on intra-articular knee injections for the treatment of degenerative cartilage lesions and osteoarthritis (OA) in sport-active patients. Methods A literature search was performed in July 2023 according to the PRISMA guidelines on three electronic databases (PubMed, Cochrane, Web of Science). Studies addressing intra-articular injections for degenerative knee ca… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
0
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 53 publications
0
0
0
Order By: Relevance
“…In a previous study by Pettit et al, it has been demonstrated how untreated cartilaginous lesions increase by 0.11 cm 2 every month and how cartilaginous lesions of the patella tend to progress more quickly towards high‐grade lesions [ 37 ]. The worse clinical results found in patients with pain for longer could be linked not only to an increase in the size of the original cartilage defect but also to degenerative processes of the surrounding cartilage [ 11 , 32 , 37 ]. There is a complex interaction of macroscopic and microscopic factors, such as altered edge stress on the defect that can lead to increased pressure, expansion and consequent increased loading on the subchondral bone [ 21 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In a previous study by Pettit et al, it has been demonstrated how untreated cartilaginous lesions increase by 0.11 cm 2 every month and how cartilaginous lesions of the patella tend to progress more quickly towards high‐grade lesions [ 37 ]. The worse clinical results found in patients with pain for longer could be linked not only to an increase in the size of the original cartilage defect but also to degenerative processes of the surrounding cartilage [ 11 , 32 , 37 ]. There is a complex interaction of macroscopic and microscopic factors, such as altered edge stress on the defect that can lead to increased pressure, expansion and consequent increased loading on the subchondral bone [ 21 ].…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, women often start from lower scores of knee function and activity level compared to men [ 15 , 30 ]. Men and women have numerous biomechanical and biological differences, and analysing the peculiarities of men and women is a pressing aspect of orthopaedics [ 11 ]. The importance of studying gender‐based specific characteristics and outcomes is confirmed by the lower scores documented in the current study in women treated with this bioscaffold for patellar defects.…”
Section: Discussionmentioning
confidence: 99%
“…Остеоартроз (ОА) -одно из самых распространенных заболеваний в мире [1,2]. На развитие ОА влияет большое число разных факторов, одним из которых является высокая физическая нагрузка на опорно-двигательную систему [3] получила вискосапплементарная терапия [4]. В данной работе уделяется внимание белкам сурфактанта, выполняющим лубрикативную функцию в легочных альвеолах.…”
unclassified